2017
DOI: 10.1177/0002764216682991
|View full text |Cite|
|
Sign up to set email alerts
|

Effectively Maintained Inequality in Educational Transitions in the Republic of Ireland

Abstract: While it is well established that the structure and organization of the education system affects youth transitions, less attention has been paid to the study of qualitative distinctions at the same level of education over time in the Irish context. Using data from the School Leavers' Survey over the period 1980-2006, this paper considers the hypothesis of effectively maintained inequality in the case of the Republic of Ireland. The data capture young people's transitions during three distinct and remarkable ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 17 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…The socio-economic status of the family impacts on students' successes in mathematics (OECD, 2016). Similarly, the income of the household and higher earnings predicts the higher levels of educational attainment (Byrne and McCoy, 2017). In this study, the effect of the demographic variables age, gender, residence, types of family, parents' education, parent's occupation and the ecological region of pupils participating in the research has not been found the greater impact in their attitude towards mathematics learning.…”
Section: Discussionmentioning
confidence: 63%
“…The socio-economic status of the family impacts on students' successes in mathematics (OECD, 2016). Similarly, the income of the household and higher earnings predicts the higher levels of educational attainment (Byrne and McCoy, 2017). In this study, the effect of the demographic variables age, gender, residence, types of family, parents' education, parent's occupation and the ecological region of pupils participating in the research has not been found the greater impact in their attitude towards mathematics learning.…”
Section: Discussionmentioning
confidence: 63%
“…Indeed, these results are interesting beyond their contribution to examine the Spanish case, as they offer evidence for the comparison between two competing hypotheses about the transformation of vertical inequality into horizontal inequality. Even though many different studies have documented the increase of horizontal inequality as educational expansion make vertical inequality to decrease (Andrew, 2017;Byrne & McCoy, 2017;Guetto & Vergolini, 2017), not so many works have studied if that result is due to the behaviour of socioeconomically advantaged students as EMI theory predicts or it is due to the behaviour of disadvantaged students as the diversion hypothesis expects. Schindler and Lörz (2012) carried out one of the few studies that have explicitly compared both hypothesis examining the evolution of educational inequality in the transition to Tertiary Education in Germany.…”
Section: Discussionmentioning
confidence: 99%
“…This body of research includes an interrogation of the very use of the term educational disadvantage with some scholars arguing that the deficit language itself perpetuates inequality (Archer and Weir 2005;Spring 2007). Similarly, scholarship focusses on ways in which the education system more broadly propagates and legitimates inequality, reproducing intergenerational advantages for dominant social groups and exposing the close relationships between education, inequality and class (Bourdieu 1996), a phenomenon which has intensified in the Irish context since the 1970s (Byrne and McCoy 2017;Fleming 2016;Harford 2018Harford , 2021Harford and Fleming 2020). Implicit in this position is the view that the values and norms promoted within the system are those of the middle classes, shaped by the concerns and needs of middle-class families in their drive to maintain and reproduce their middle-class advantage (Ball 2003;Reay 2011), thus reproducing social inequalities by conferring a range of advantages on the already advantaged (Bourdieu and Passeron 1990).…”
Section: Educational Disadvantagementioning
confidence: 99%